Model Learning Cycle 5E terhadap Kemampuan Pemecahan Masalah Matematika - Efuansyah Efuansyah; Reny Wahyuni; Drajat Friansah; Trie Ayu Wulandari (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
This study aimed to determine whether there is an effect of the Learning Cycle 5E learning model on the mathematical problem-solving ability of class XI students of senior high school in Lubuklinggau. Type of research was true experimental design, which is an experiment that is considered to be good because it meets the requirements in the experiment, namely the presence of other groups that have not experienced the experiment observed so that changes that occur between before the research and after the research are really visible. As the population is all students of class XI of senior high school in Lubuklinggau consisting of 131 students and the sample of the experimental class is class XI.MIA.2, and as the control class is class XI.MIA.1, both classes are selected at random. Data collection was carried out using test techniques, namely pre-test and post-test. Then the data collected was analyzed using a t-test. Based on the results of the study it can be concluded that there is an effect of the 5E Learning Cycle model on the mathematical problem-solving ability of class XI students of senior high school in Lubuklinggau.